2011
DOI: 10.1080/12265934.2011.635880
|View full text |Cite
|
Sign up to set email alerts
|

Main factors associated with homeowners' intentions to move

Abstract: Individuals make mobility decisions based on many factors. Satisfaction with neighbourhoods and homes has been identified in previous research, as have changing demographic characteristics. This paper extends earlier studies to identify the main factors behind the intentions to move for non-moving homeowners versus those who subsequently moved using data from a survey conducted for Franklin County homeowners in Ohio in the US, through factor analysis and Ordered Logistic Regression (OLR) analysis. Non-movers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…On the housing component, the questionnaire employs the dwelling features dimension consisting of satisfaction with the living room (Opoku & Abdul Muhmin, 2010), kitchen (Andersen, 2011), dining room (Salleh, 2008), bedroom (Woo & Morrow-Jones, 2011), bathroom (Elsinga & Hoekstra, 2005) and design of room arrangement (Jansen, 2014); while the dwelling utility emphasizes the residents' satisfactions toward electical and water supply (Salleh, 2008). On the neighbourhood component, the residents are inquired about their satisfaction level towards the availability of neighbourhood facilites within their neighbourhood such as hospital, community hall, police station, market (Mohit & Azim, 2012) and mini mart (Salleh, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the housing component, the questionnaire employs the dwelling features dimension consisting of satisfaction with the living room (Opoku & Abdul Muhmin, 2010), kitchen (Andersen, 2011), dining room (Salleh, 2008), bedroom (Woo & Morrow-Jones, 2011), bathroom (Elsinga & Hoekstra, 2005) and design of room arrangement (Jansen, 2014); while the dwelling utility emphasizes the residents' satisfactions toward electical and water supply (Salleh, 2008). On the neighbourhood component, the residents are inquired about their satisfaction level towards the availability of neighbourhood facilites within their neighbourhood such as hospital, community hall, police station, market (Mohit & Azim, 2012) and mini mart (Salleh, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire also incorporates neighbourhood accesibility measurements such as residents' satisfaction levels with travel time to activity places with less traffic jam (Woo & Morrow-Jones, 2011) and home-work travel distance (Witten et al, 2008). The public transportation dimension places an emphasis on satisfaction levels with frequency of bus service (Pacione, 2003), availability of public transport (Go & Lee, 2012) and facilities at the bus stop (Day, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actual mobility and mobility intentions are commonly used as indicators of residential mobility patterns. Studies showed that actual mobility, mobility intention and residential satisfaction are all highly correlated (Woo & Morrow-Jones, 2011;.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Residents in turn develop a strong sense of belonging and attachment to their housing and neighbourhood, most possibly with no intention of leaving their neighbourhood in future. Key neighbourhood attributes of physical environment, greenery, facilities, economic livelihood, social interaction, social attachment, dwelling features and utilities can affect mobility decisions and residential relocation choices (Woo & Morrow-Jones, 2011). Thus, this study aims to examine the linkages between tenure ownership and mobility decisions, and residents' perceptions of their housing and neighbourhood quality.…”
Section: Introductionmentioning
confidence: 99%